The effect of smoke-free policies on hospitality industry revenues in Cyprus: An econometric approach - Talias, Michael A.; Savva, Christos S.; Soteriades, Elpidoforos Soterakis; Lazuras, Lambros (My University, 2015)
Objective Smoke-free policies aiming to improve quality of indoor air and significantly reduce exposure to secondhand smoke in the hospitality industry are faced with strong opposition from the tobacco industry and hospitality venue owners claiming that they lead to reductions of revenues. The objective of our study was to examine the impact of a recently introduced smoke-free legislation on the revenues of the hospitality industry in Cyprus. Methods Anonymous information on revenues was obtained from the Cyprus government value added tax office for the entire hospitality industry in Cyprus including hotels, bars, restaurants and cafeterias between 2005 and 2011. Panel data methodology was used to examine the effect of a smoke-free legislation, on tourism, businesses’ revenues adjusting for gross domestic product, inflation, unemployment rate, tourists’ arrivals, seasonal variation and the economic crisis. Results Our study showed that the implementation of the smoke-free policy did not have negative effects on the hospitality industry profitability. Conclusions We conclude that even in regions with relatively high smoking rates, pro-smoking societal attitudes and weak social norms against tobacco control, and even during periods of economic crisis, smoke-free legislation does not impact negatively on hospitality industry revenues and if anything may lead to a small positive increase.
Keywords: Economics; Public opinion; Social marketing; Smoke-free policy; Smoking; Tobacco smoke pollution; Restaurants; Cyprus